2006
DOI: 10.1007/s11172-006-0344-6
|View full text |Cite
|
Sign up to set email alerts
|

α-Ureidoalkylation of thiosemicarbazide and aminoguanidine

Abstract: Optimum conditions for the targeted synthesis of 5,7 dialkyl 3 thioxoperhydroimid azo[4,5 e] [1,2,4]triazin 6 ones, 4,5 bis(3 thiosemicarbazido(guanidinoamino))imidazolidin 2 ones, and 1,3 dialkyl 4 (guanidinoimino)imidazolidin 2 ones by α ureidoalkylation of thiosemicarbazide or aminoguanidine were found. A novel conglomerate in the series of imidazolidin 2 one derivatives was detected: 4,5 bis(guanidinoamino) 1,3 dimethylimid azolidin 2 one dihydrochloride dihydrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Previously unknown 4,5 bis[thiosemicarbazido(guanidinoamino)]imidazolidine 2 thiones, 5,7 dialkylperhydroimidazo[4,5 e] [1,2,4]triazine 3,6 dithiones, 4,6 diethyl 5(3H) thioxotetrahydro 1H imidazo[4,5 c][1,2,5]thiadiazole 2,2 dioxide, and 1,3 dialkyl 4 [guanidinoimino(arylsulfonylimino)]imidazolidine 2 thiones have been synthesized. Key words: α thioureidoalkylation, thiosemicarbazide, aminoguanidine, sulfamide, 4,5 dihydroxyimidazolidine 2 thiones, 4,5 bis[thiosemicarbazido(guanidinoamino)]imidazol idine 2 thiones, 5,7 dialkylperhydroimidazo[4,5 e][1,2,4]triazine 3,6 dithiones, 4,6 diethyl 5(3H) thioxotetrahydro 1H imidazo[4,5 c][1,2,5]thiadiazole 2,2 dioxide, 1,3 dialkyl 4 [guanidinoimino(arylsulfonylimino)]imidazolidine 2 thiones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously unknown 4,5 bis[thiosemicarbazido(guanidinoamino)]imidazolidine 2 thiones, 5,7 dialkylperhydroimidazo[4,5 e] [1,2,4]triazine 3,6 dithiones, 4,6 diethyl 5(3H) thioxotetrahydro 1H imidazo[4,5 c][1,2,5]thiadiazole 2,2 dioxide, and 1,3 dialkyl 4 [guanidinoimino(arylsulfonylimino)]imidazolidine 2 thiones have been synthesized. Key words: α thioureidoalkylation, thiosemicarbazide, aminoguanidine, sulfamide, 4,5 dihydroxyimidazolidine 2 thiones, 4,5 bis[thiosemicarbazido(guanidinoamino)]imidazol idine 2 thiones, 5,7 dialkylperhydroimidazo[4,5 e][1,2,4]triazine 3,6 dithiones, 4,6 diethyl 5(3H) thioxotetrahydro 1H imidazo[4,5 c][1,2,5]thiadiazole 2,2 dioxide, 1,3 dialkyl 4 [guanidinoimino(arylsulfonylimino)]imidazolidine 2 thiones.…”
mentioning
confidence: 99%
“…1-5 α Ureidoalkylation of thiosemicarbazide, aminoguanidine, and sulfamides yielded 5,7 dialkyl 3 thioxoperhydroimidazo [4,5 e] [1,2,4]tri azin 6 ones (1), 2 4,5 bis(thiosemicarbazido) and 4,5 bis (guanidinoamino)imidazolidin 2 ones (2, 3), 2 4 (guani dinoamino) and 4 (sulfonylimino)imidazolidin 2 ones (4-6), 2-4 and 5(3H) thioxotetrahydro 1H imidazo [4,5 c] [1,2,5]thiadiazole 2,2 dioxides (7). 5 Only few examples of the synthesis of glycoluril heteroanalogs by condensation of ureas with 4,5 dihydroxy imidazolidine 2 thiones (DHIT) have been published.…”
mentioning
confidence: 99%
“…4,5 Dihydroxyimidazolidine 2 ones (DHI) are wide ly used as building blocks for the synthesis of various het erocyclic compounds, in particular, tetrahydroimidazo [4,5 d]imidazoles, 1-6 octahydroimidazo[4,5 e] 1,2,4 tri azines, 7, 8 and tetrahydroimidazo[4,5 с] 1,2,5 thiadi azoles. 9, 10 The use of thio analogs of DHI, i.e., 4,5 dihydroxyim idazolidine 2 thiones (DHIT), in the synthesis of the cor responding heterocyclic systems is less studied because these compounds are less available.…”
mentioning
confidence: 99%
“…In recent years, we have extensively studied α ureido alkylation of ureas, 2 sulfamides, 3-5 sulfonamides, 4,5 ureido alcohols, 6 ureido acids, 6,7 thiosemicarbazide, and aminoguanidine (in the hydrochloride form) 8, 9 with cy clic vicinal ureidobis(α carbinols) 2 containing two po tential α ureidoalkylating sites. We have developed gen eral methods for the targeted synthesis of various N sub stituted glycolurils 1, including those containing hydr oxy(carboxy)alkyl substituents, and their sulfur analogs.…”
mentioning
confidence: 99%
“…Enantiomerically pure glycolurils have been first obtained by diastereoselective or diastereospecific α ureidoalkyla tion of optically pure N carbamoyl α amino acids. 10, 11 We have found that α ureidoalkylation of sulfamide, sul fonamides, and aminoguanidine hydrochloride gives, via unusual formation of the C=N bond, 4(5) sulfonyl imino (4) and guanidinoiminoimidazolidin 2 ones (5) (see Refs 4,5,9). The second pathway of the reaction of Here we systematically investigated two step α ureido alkylation of various ureas (1 alkyl , 1 aryl , 1 (2 pyri midyl) , and 1,1 dialkylureas and imidazolidin 2 one (ethyleneurea) 12 ) with DHI.…”
mentioning
confidence: 99%